Residential Load Reduction Scheduling with Optimal Power Flow and Segmented Incentives - Yu, Ziwen; You, Pengcheng; Yang, Zaiyue (IEEE Power & Energy Society General Meeting, 2018)
In this paper, we formulate an optimal scheduling problem for demand response (DR) that schedules residential electrical appliances load to shave peak load. The schedule aims to minimize the total incentive cost and power loss over the power flow variables, subject to load capacity of users, grid operational constraints and the AC power flow equations. To deal with the nonconvexity of power flow equations, we present a solution based on second-order cone programming (SOCP) relaxation of optimal power flow. Furthermore, if the SOCP relaxation is exact, our algorithm yields a globally optimal solution. Finally, we evaluate the performance of our method by numerical simulations, which indicate that it is efficient and flexible.